El milagro hagiográfico en Gonzalo de Berceo: articulaciones narratológicas. - González, Javier Roberto (Scripta Mediaevalia, 2026)
The narration of miracles, one of the distinctive features of hagiographies or lives of saints during the Middle Ages, is a resource extensively employed by Gonzalo de Berceo in his two major Vidas, dedicated to San Millán de la Cogolla and Santo Domingo de Silos. However, criticism has not paid the same attention to defining the features of the hagiographic miracle as a micro-narrative as it has to the structural characterization of the framing hagiographic macro-narrative. This article aims to establish and substantiate in detail the narrative characteristics of Berceo's hagiographic miracle, always in contrast to those of the Marian miracle, which is very different in form and meaning. To this end, the belonging of hagiography to a purely heroic matrix is proposed and substantiated, the structural and semantic relationships that the miraculous micro-narratives establish with the hagiographic macro-narrative that frames them are analyzed, and finally, in contrast to other critical proposals that establish more detailed partitions, the absolute functional relevance of the division into three books that Berceo provides for his two Vidas is postulated, which arises naturally from the progression of the heroic project of the protagonists through the performance of miracles.